At the Heart of Christian Worship : Liturgical Essays of Yves Congar - Congar, Yves, 1904-1995 (Book collections on Project MUSE., 2010)
"Cardinal Yves Congar is universally known and respected as the great ecclesiologist of Vatican II whose seminal ideas helped to reconfigure the landscape of Catholic theology following the council. Less well known is his role in contributing far-reaching insights to the emerging liturgical movement in the church. This collection represents several of Congar's decisive contributions. Reading them makes possible a deeper and more cogent reception of the key ideas of the council documents. These texts are at once both erudite and exciting, both essential and pastorally incisive. There has never been a better time to disseminate these critically important liturgical insights than the present moment. 'The essays translated here are a treasure trove of theological reflection linking liturgy to ecclesiology. They are as fresh today as they were when Congar first wrote them. We are in Paul Philibert's debt.' (John F. Baldovin, SJ, Professor of Historical and Liturgical Theology Boston College School of Theology and Ministry). 'These essays combine immense erudition with arguments that are accessible to the nonspecialist. They offer a rare combination of passion and precision, and they are at least as relevant today as when they were first published.' (Timothy Radcliffe, OP Author of What Is the Point of Being a Christian? and Why Go to Church? The Drama of the Eucharist)."--